Aggressive behaviour among drug-using women from Cape Town, South Africa: Ethnicity, heavy alcohol use, methamphetamine and intimate partner violence - Carney, T.; Myers-Franchi, Bronwyn; Kline, T.L.; Johnson, K.; Wechsberg, W.M. (BMC, 2017)
Background: Women have generally been found to be the victims of violence, but scant attention has been paid to the characteristics of women who perpetrate aggression and violence. In South Africa, violence is a prevalent societal issue, especially in the Western Cape.